ROCK SLOPE STABILITY ANALYSIS ALONG A TRANSPORTATION CORRIDOR IN NORTHERN VIETNAM USING BLOCK THEORY AND PROBABILISTIC APPROACH - Quoc Phi Nguyen1*, Thi Mai Hoa Phan1, Thao Vu Thi Phuong1, Thi Cuc Nguyen1, Hoa Nguyen Thi1, Duc Le Huynh1, Ha Tran Thi Thu1, Thanh Phi Truong2 (Chelonian Research Foundation, 2024)
The stability of rock slopes is mainly dependent on geological characteristics such as discontinuities inside the rock mass and its mechanical behaviour. In this study, the stability of rock slope is conducted in two steps: First, the unstable blocks are identified using Block theory and then, the potential failure of rock blocks are analysed using probability approach. The application of Block Theory helps finding potential failure rock blocks (key blocks) and then, their location, volume and geometry (shape, size) can also be identified on slope surface. However, there are many factors can affect the stability of rock slopes, such as the orientation and dip angle of slope face and fractures, the cohesion and friction angle of discontinuities, the strength properties, etc, and the uncertainty of input parameters were considered as data ranges for probability analysis. The final factor of safety (FS) of each failure mode is calculated using limit equilibrium method. In order to verify the developed procedure, the field survey data of rock slopes along provincial road DT.206 at Trung Khanh area of Cao Bang province were analysed. Results could significantly help the field engineer to decide which portion of slope need immediate supports. The integrated approach provides a mathematical formulation that enables the engineer to relate the rock structures to the excavation surface and analyse the stability of rock slope under probability functions of collected data.